Fenomena Kecanduan Membaca Manhwa pada Pecinta Manhwa Daring di Kalangan Remaja dan Dewasa Muda Indonesi: Literature Review - Lubis, Winda Safutri; Primanita, Rida Yanna (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The phenomenon of addiction to reading South Korean comics or manhwa is becoming increasingly widespread in Indonesia, especially among teenagers and young adults, as access to digital comic platforms increases. The purpose of this article is to systematically review research findings on the psychological, social, and technological factors that influence addiction to reading online manhwa and its impact on individual well-being. The method used is a literature review by examining ten relevant open access scientific articles, obtained from various academic sources and discussing the behaviour of online comic readers on digital platforms such as LINE Webtoon, Webtoon, Tapas, and KakaoPage. The analysis was carried out by grouping the research findings based on the driving factors and the impacts caused. The results of the study show that addiction to reading manhwa is influenced by the need for emotional escape, feelings of loneliness, motivation for entertainment, and ease of access through digital devices such as smartphones, tablets, and laptops. On the other hand, reading manhwa also has positive impacts, such as improving visual literacy and imagination. However, if left unchecked, this habit has the potential to lead to digital addiction, which can interfere with concentration in studies and the balance of daily activities.